Ilexpublesnins C–M, Eleven New Triterpene Saponins from the Roots of Ilex pubescens - Zhou, Yuan; Chai, Xing-Yun; Zeng, Ke-Wu; Zhang, Jia-Yu; Li, Ning; Jiang, Yong; Tu, Peng-Fei (Planta Medica, 2013)
Eleven new triterpene saponins, ilexpublesnins C–M (1–11), along with ten known analogues were isolated from the roots of Ilex pubescens. Their structures were elucidated on the basis of extensive spectroscopic analysis, including 1D and 2D NMR experiments. Compounds 1, 2, 10, and 11 contain a 24-aldehyde, which is rare for triterpene saponins from Ilex. These compounds were evaluated in vitro for their cytotoxic effects on human cancer cell lines HepG2, HLE, BEL7402, BEL7403, BEL7405, MCF-7, and HeLa. Among them, only compounds 6 and 19 showed cytotoxicity against the MCF-7 cell line [inhibition (%): 33.14 and 34.03, respectively].
Keywords: Ilex pubescens; Aquifoliaceae; ilexpublesnins C–M; triterpene saponin; 24-aldehyde group; cytotoxicity